MENELANJANGI MATRIKS HETEROSEKSUAL DALAM NOVEL MIDDLESEX KARYA JEFFREY EUGENIDES DAN GOLDEN BOY KARYA ABIGAIL TARTTELIN - Sri Nurhidayah; Apsari Fajar Prihantini (Universitas Andalas, 2017)
This research is aimed to disclose the demolishing of the Heterosexual Matrix in Jeffrey Eugenides's Middlesex and Abigail Tarttelin’s Golden Boy. In Eugenides’s Middlesex and Tarttelin’s Golden Boy, both characters Cal/Calliope and Max are intersex characters who have ambiguous genitalia known as intersex seek for his/her gender identity, but the two characters do not commit to plastic surgery for adhering gender norm. Thus, the problem raises whether both characters reproduce the Heterosexual Matrix or not. Judith Butler’s concept of gender is used to analyze gender problems. Based on the research conducted, the result shows that Cal/Calliope and Max seems to get trapped in Heterosexual Matrix because the binary gender will be still exist although subjects tries to get away from Heterosexual Matrix. Keywords: gender, intersex, Heterosexual matrix